HUBUNGAN ANTARA BERPIKIR POSITIF DAN EFIKASI DIRI DENGAN KECEMASAN BERBICARA DI DEPAN UMUM PADA MAHASISWA PROGRAM STUDI ILMU KOMUNIKASI UNIVERSITAS X JAKARTA - Agustine Wahyu Adi Christininingsih & Rahma Widyana (Jurnal Psikologi, 2017)
Objective of this research was to verify the relationship between positive thinking and selfefficacy with public speaking anxiety. This research was interesting since respondents werestudents of the communication department of university X in Jakarta. Ninety studentsparticipated in this research. This research revealed 3 things. Firstly, there was a significantand negative correlation between positive thinking with public speaking anxiety rxy= -.224,p= .034. Secondly, there was also a significant and negative correlation between self-efficacywith public speaking anxiety, rxy= -.252, p= .017. Thirdly, the linier multivariate regressionanalysis revealed that public speaking anxiety was predicted by student’s positive thinking andself-efficacy, F= 12.492, p= .029. Several limitation and suggestions for future research wereexplained at the discussion point.Key words: Public speaking anxiety, positive thinking, self-efficacy.